Experimental Study and Simulation of Solid-Liquid Flows in Wet Beadmil using YADE-OpenFOAM Coupling - Fenda Florena, Fenfen
Nanoparticles find its application in various fields. Apart from that nanoparticles tend to agglomerate which will alter its physical and chemical properties, making it incompatible for the preferred application. To overcome this, dispersion of nanoparticle is desirable which could prevent the agglomeration and provide a good dispersion stability by retaining its properties. One of the most productive technique for the dispersion of nanoparticles is beads milling process. In the other hand, experimental works to investigate the detailed hydrodynamics and flow pattern in the whole system of bead mill is complicated and high cost. Numerical modeling offers a method to predict the detailed hydrodynamics and flow pattern in the entire system inexpensively. The integration of DEM for solid phase and SPH models for liqudi phase were carried out to simulate the mixing behavior in wet bead mill. The effect of rotation speed of 1,200 and 1,800 rpm on the particle size distribution was discussed. For rotation speed of 1,800 rpm, the particles are well dispersed resulting in a good dispersion stability.